Liming in the sugarcane burnt system and the green harvest practice affect soil bacterial community in northeastern São Paulo, Brazil - Val-Moraes, Silvana Pompeia [UNESP]; de Macedo, Helena Suleiman [UNESP]; Kishi, Luciano Takeshi [UNESP]; Pereira, Rodrigo Matheus; Navarrete, Acacio Aparecido; Mendes, Lucas William; de Figueiredo, Eduardo Barretto [UNESP]; La Scala, Newton [UNESP]; Tsai, Siu Mui; de Macedo Lemos, Eliana Gertrudes [UNESP]; Alves, Lúcia Maria Carareto [UNESP] (Springer Nature, 2016)
Here we show that both liming the burnt sugarcane and the green harvest practice alter bacterial community structure, diversity and composition in sugarcane fields in northeastern São Paulo state, Brazil. Terminal restriction fragment length polymorphism fingerprinting and 16S rRNA gene cloning and sequencing were used to analyze changes in soil bacterial communities. The field experiment consisted of sugarcane-cultivated soils under different regimes: green sugarcane (GS), burnt sugarcane (BS), BS in soil amended with lime applied to increase soil pH (BSL), and native forest (NF) as control soil. The bacterial community structures revealed disparate patterns in sugarcane-cultivated soils and forest soil (R = 0.786, P = 0.002), and overlapping patterns were shown for the bacterial community structure among the different management regimes applied to sugarcane (R = 0.194, P = 0.002). The numbers of operational taxonomic units (OTUs) found in the libraries were 117, 185, 173 and 166 for NF, BS, BSL and GS, respectively. Sugarcane-cultivated soils revealed higher bacterial diversity than NF soil, with BS soil accounting for a higher richness of unique OTUs (101 unique OTUs) than NF soil (23 unique OTUs). Cluster analysis based on OTUs revealed similar bacterial communities in NF and GS soils, while the bacterial community from BS soil was most distinct from the others. Acidobacteria and Alphaproteobacteria were the most abundant bacterial phyla across the different soils with Acidobacteria Gp1 accounting for a higher abundance in NF and GS soils than burnt sugarcane-cultivated soils (BS and BSL). In turn, Acidobacteria Gp4 abundance was higher in BS soils than in other soils. These differential responses in soil bacterial community structure, diversity and composition can be associated with the agricultural management, mainly liming practices, and harvest methods in the sugarcane-cultivated soils, and they can be detected shortly after harvest.